7(9x-3)-4(2x-1)=

Simple and best practice solution for 7(9x-3)-4(2x-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(9x-3)-4(2x-1)= equation:


Simplifying
7(9x + -3) + -4(2x + -1) = 0

Reorder the terms:
7(-3 + 9x) + -4(2x + -1) = 0
(-3 * 7 + 9x * 7) + -4(2x + -1) = 0
(-21 + 63x) + -4(2x + -1) = 0

Reorder the terms:
-21 + 63x + -4(-1 + 2x) = 0
-21 + 63x + (-1 * -4 + 2x * -4) = 0
-21 + 63x + (4 + -8x) = 0

Reorder the terms:
-21 + 4 + 63x + -8x = 0

Combine like terms: -21 + 4 = -17
-17 + 63x + -8x = 0

Combine like terms: 63x + -8x = 55x
-17 + 55x = 0

Solving
-17 + 55x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '17' to each side of the equation.
-17 + 17 + 55x = 0 + 17

Combine like terms: -17 + 17 = 0
0 + 55x = 0 + 17
55x = 0 + 17

Combine like terms: 0 + 17 = 17
55x = 17

Divide each side by '55'.
x = 0.3090909091

Simplifying
x = 0.3090909091

See similar equations:

| 3(3b-4)=2+7b | | x-3/4=-5/3 | | -9/4=3x/20 | | 5a-2=2(a-4) | | b^3=-8 | | 2.8+x=3.1 | | 6t-20=13 | | 10x^2-y+x^2= | | K^2+13k+12=0 | | 16-2n-5=8n+65 | | 3y=2x+3 | | 2(x+6)=3(x-1)-15 | | r^4+30r^2=11r^3 | | 5.1x+4=4.1x | | 4x^4=100x^2 | | 1.6x+x=61 | | 4z^3=4z^2+24z | | y^3-3y^2+2y=0 | | 10x^2=20x+80 | | =7h+40 | | 2w+3(w+4)=27 | | 8*(0.5x-1)=12 | | 6*(x-2)=4*(x+4) | | 2x+2y-12=0 | | 3*(x-1)=2*(x-4) | | 16-7d=-3d-2 | | 5*(x+3)=35 | | 3x+2=10-x | | 2x+9=-29 | | 5d-4=-19 | | 6a+1=-5 | | 12+4p=4 |

Equations solver categories